2016
DOI: 10.1007/s00431-016-2807-6
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes screening in overweight and obese children and adolescents: choosing the right test

Abstract: HbA1c seems to be more reliable than OGTT for diabetes screening in overweight and obese children and adolescents. The optimal HbA1c threshold for identifying patients with diabetes was found to be 42 mmol/mol (6.0%). What is Known: • The prevalence of obesity is increasing and health problems related to type 2 DM can be serious. However, an optimal screening test for diabetes in obese youth seems to be controversial in the literature. What is New: • In our study, the ROC analysis revealed for FPG an optimal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
2
19
1
Order By: Relevance
“… 24 25 26 27 While the previous four studies in the pediatric populations only suggested an optimal cutoff point for prediabetes, we also evaluated the cutoff point for type 2 DM. In a recent study, Ehehalt et al 28 also reported an optimal HbA1c cutoff point for diabetes of 6.0%, with a sensitivity of 94.0% and a specificity of 92.9% in 4,848 German children. The differences in HbA1c cutoff points may reflect differences in study populations.…”
Section: Discussionmentioning
confidence: 95%
“… 24 25 26 27 While the previous four studies in the pediatric populations only suggested an optimal cutoff point for prediabetes, we also evaluated the cutoff point for type 2 DM. In a recent study, Ehehalt et al 28 also reported an optimal HbA1c cutoff point for diabetes of 6.0%, with a sensitivity of 94.0% and a specificity of 92.9% in 4,848 German children. The differences in HbA1c cutoff points may reflect differences in study populations.…”
Section: Discussionmentioning
confidence: 95%
“…Glycosylated hemoglobin or HbA1c is an established marker for long-term glycemic control in patients with diabetes [ 33 ]. HbA1c has been proposed as a screening tool for undiagnosed diabetes in adults [ 6 ] and children with overweight or obesity [ 8 ], but the evidence is still very limited. We found very little change in HbA1c levels from childhood to late adolescence, and there was no difference between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance plays an important role in the development of youth-onset type 2 diabetes, an emerging disease in children and youth [ 4 ]. Homeostasis model assessment estimates insulin resistance (HOMA-IR) from fasting levels of insulin and glucose [ 5 ]; other measures that have been used to identify insulin resistance or diabetes include fasting insulin and glycosylated hemoglobin (HbA1c), respectively [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In several studies and current recommendations, it had been concluded that HbA 1c can identify children with PD with similar confidence as compared with fasting glucose and OGTT 2-h glucose 7 , 8 , 47 . However, studies investigating the specificity and sensitivity for identifying PD found only low predictable value for HbA 1c , both in adults 48 – 50 and in Ob children and adolescents 8 , 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes, IFG and IGT are defined by glucose measures in the fasting state, as well as at 2-h during a standardized oral glucose tolerance test (OGTT). However, recent evidence shows that glucose and hemoglobin A 1c (HbA 1c ) levels rise already before the clinical diagnosis of diabetes 7 , 8 , allowing diagnosis of PD defined by IFG or IGT well before the onset of diabetes mellitus. According to recent ADA guidelines, to test for PD, fasting plasma glucose, OGTT 2-h blood glucose (BG) and HbA 1c levels, are considered as equally appropriate 7 .…”
Section: Introductionmentioning
confidence: 99%